Knowledge and practice on tuberculosis infection control among healthcare workers in Lembah Pantai district, Kuala Lumpur - Ramlan, Waramlah (2017)
Introduction: Tuberculosis (TB) is the leading cause of mortality among infectious diseases in the world. Healthcare workers (HCWs) are among the high risk groups of getting TB and the prevalence is double that of the general population. This is due to workplace exposure to TB patients, without adequate TB infection control practices. In Malaysia, the number of TB cases among HCWs has increased from year to year, however TB infection control (TBIC) knowledge and practice remain poor.